The Canadian Congenital Diaphragmatic Hernia Collaborative Mobile App: A National Guideline Implementation Strategy - LaRusso, Kathryn; Puligandla, Pramod S.; Anna, Guilherme Sant' (American Journal of Perinatology, 2020)
Objective Coinciding with the publication of the Canadian congenital diaphragmatic hernia (CDH) Collaborative's clinical practice guidelines (CPG), we developed a mobile smartphone app to increase guideline utilization and promote knowledge translation.Study Design This mobile app was organized into sections corresponding to the phases of CDH care (prenatal, perinatal/postnatal, and child/adolescent), and contained 22 recommendations supported by evidence summaries, PubMed links, levels of evidence, and strength of expert consensus. Download statistics were collected from September 2018 to June 2020 after release of two iOS versions and an Android platform. Data regarding user numbers/location, most visited sections, and individual session details were analyzed.Results During the study period, the CDH app had 1,586 users predominantly from Canada (40%), United States (30%), and Brazil (12%). The Android release increased app visibility, particularly in Brazil, which had the largest number of new users. Of 3,723 sessions, roughly one-third were returning users. The average session duration and screens viewed/session was 4 minutes and seven screens, respectively. Postnatal ventilation was the most frequently visited subsection after prenatal diagnosis/risk stratification. Measurement of observed-to-expected lung head ratio was the most visited individual recommendation. The guideline compliance checklist was the most frequently accessed resource highlighting its utility.Conclusion The CDH app is an innovative platform to disseminate guidelines. The increasing global reach of the app suggests worldwide CPG relevance. With additional features planned, the CDH app will continue to support clinical decision-making and empower patients and families as they navigate the short and long-term challenges associated with CDH.Key Points
Keywords: congenital diaphragmatic hernia; mobile app; clinical practice guidelines